Randomized Controlled Trials and Quasi-Experimental Therapies for Hoarding Disorder: A Review of the Literature - Hidayati, Nur Oktavia; Nida, Nazla; Shalahuddin, Iwan (Jordan Medical Journal, 2023)
Aims: This study identified therapies for hoarding disorder. Methods: The literature review method was employed with several databases: EBSCOhost, PubMed, Sage Journals, and ScienceDirect, and the Google Scholar search engine. Articles were sorted based on the following inclusion criteria: published between 2011–2021, written in Indonesian or English, available full-text, type of experimental study (RCT, quasi), focus on hoarding or compulsive hoarding and its effects on daily life, and including a sample for a primary study with adult and elderly hoarders aged 19 plus. Results: Five articles were found discussing therapies using an experimental method of treating hoarding disorder. The findings showed improvement in hoarding symptoms with outcomes of 23–28% for support group therapy, 31.8% for contingency management therapy, 38% for cognitive rehabilitation and exposure/sorting therapy (CREST), 43% for community-based CREST, and four out of six (66.67%) participants experiencing clinically significant changes following clutter buddies therapy. Conclusion: The procedures, periods, and number of sessions allotted to each study could have influenced the effectiveness of the intervention. However, since only one study used an RCT, further research is recommended using this method regarding therapies for hoarding disorder.